O10.3 High curable STI prevalence and incidence among young african women initiating PrEP in HPTN 082. (14th July 2019) - Delany-Moretlwe, Sinead; Mgodi, Nyaradzo; Bekker, Linda-Gail; Baeten, Jared; Pathak, Subash; Donnell, Deborah; Lennon, Denni; Rose, Scott; Makgamathe, Keolopile; Kassim, Sheetal; Mukaka, Shorai; Noble, Heather; et al.
Abstract : Background: African women face overlapping HIV and STI risks. PrEP programs among men who have sex with men have seen high STI incidence, but few data from African women taking PrEP are available Methods: HPTN 082 was conducted in Cape Town, Johannesburg (South Africa) and Harare (Zimbabwe) to evaluate uptake and adherence to daily oral PrEP in young African women. Sexually active HIV-negative women ages 16–25 were enrolled. Enrollment vaginal swabs were tested for gonorrhea (GC) and chlamydia (CT) by nucleic acid amplification, and trichomonas (TV) by rapid test. Syphilis serology was assessed. All women with positive test results received treatment. Repeat testing was conducted at 6 and 12 months. Results: Of the 412 women who initiated PrEP, median age was 21 years, 84% reported a primary sex partner and a median of 4 vaginal sex acts (IQR 2, 8) in the prior month; 35% reported that they never or rarely used condoms. At enrollment 29% of women had CT, 8% GC, 7% TV and 2% reactive syphilis serology. STI incidence was 29.6 per 100 person-years (py) for CT (95% CI 24.3, 35.4), 11.8 per 100 py for GC (95% CI 8.7, 15.7), and 7.1 per 100 py for TV (95% CI 4.7, 10.2). The majority of incident STIs were new infections: 79 of 119 CT infections, 41 of 48 GC infections, and 23 of 29 TV infections diagnosed were in women who did not have these infections at enrollment. The majority of these infections were asymptomatic. Conclusion: The prevalence and incidence of treatable STIs were high among young African women initiating PrEP. Diagnostic STI testing is important and innovative strategies that reduce STI acquisition, complications, and their potential impact on future fertility, need evaluation within the context of PrEP services where currently syndromic STI management is the standard of care. Disclosure: No significant relationships.